Photonic band gap and defect mode of one-dimensional photonic crystal coated from a mixture of (HMDSO, N2) layers deposited by PECVD. (April 2017) - Amri, R.; Sahel, S.; Gamra, D.; Lejeune, M.; Clin, M.; Zellama, K.; Bouchriha, H.
Abstract: One dimensional photonic crystal based on a mixture of an organic compound HMDSO and nitrogen N2, is elaborated by radiofrequency Plasma Enhanced Chemical Vapor Deposition (RF-PECVD) at different radiofrequency powers. The variation of the radiofrequency power for a flow of N2 /HMDSO ratio equal to 0.4, leads to obtain two kinds of layers A and B with refractive index nA  = 2 and nB  = 1.55 corresponding to RF power of 200 W and 20 W, respectively. The analysis of the infrared results shows that these layers have the same chemical composition element with different structure. These layers, which exhibit a good indexes difference (nA - nB ) contrast, allowed then the elaboration of a one-photonic crystal from the same initial gas mixture, which is the aim of this work. After the optimization of the layers thickness, we have measured transmission and reflection spectra and we found that the photonic band gap (PBG) appears after 15 periods of alternating A and B deposited layers. The introduction of defect in the structure leads to obtain a localized mode in the center of the PBG corresponding to the telecommunication wave length 1.55 μm. Finally, we have successfully interpreted our experimental results by using a theoretical model based on transfer matrix method. Highlights: A one-dimensional photonic crystal is elaborated from an organic compound HMDSO and Nitrogen N2, by PECVD. The variation of the RF power leads to obtain two layers A and B with a good refractive index contrast. These alternating A/B layers give rise to a photonic crystal for a certain number of periods. The photonic crystal is made from the same gas mixture deposited by PECVD under different conditions. The incorporation of an appropriate defect, introduces a localized mode at 1550 nm into the photonic band gap.